Chelation-mediated synthesis of nanoporous gold at near-neutral pH and room temperature by free corrosion dealloying of gold-copper alloy driven by oxygen reduction. (15th July 2021) - Welborn, Samuel S.; Simafranca, Alexander; Wang, Zeyu; Wei, Heng; Detsi, Eric
Abstract: Dealloyed nanoporous gold (NP-Au) is commonly created with hazardous chemicals including strong oxidizing acids. This work presents a green alternative to the common methods for making NP-Au. In this work, we create NP-Au by free corrosion dealloying of a Au-Cu parent alloy at room temperature in a near-neutral pH aqueous solution of ethylenediaminetetraacetic acid (EDTA), a non-toxic chelating ligand. The oxygen reduction reaction (ORR), catalyzed by activated carbon cloth (ACC), is employed to drive selective oxidation of Cu into Cu 2+ ions, and EDTA is used to sequester the Cu 2+ ions, preventing passivating copper oxide (CuOx)-forming reactions. We call this methodology chelation-mediated dealloying. Using small-angle x-ray scattering (SAXS), x-ray diffraction (XRD), and scanning electron microscopy (SEM), we observe that the NP-Au produced under mild conditions is similar to that produced by free corrosion dealloying in nitric acid (HNO3 ), a highly hazardous and strong oxidizing acid. Graphical abstract: Image, graphical abstract